Cardiac complications of congenital disorders of glycosylation (CDG): a systematic review of the literature. Issue 5 (19th July 2017) - Marques‐da‐Silva, D.; Francisco, R.; Webster, D.; dos Reis Ferreira, V.; Jaeken, J.; Pulinilkunnil, T.
Abstract: Congenital disorders of glycosylation (CDG) are inborn errors of metabolism due to protein and lipid hypoglycosylation. This rapidly growing family of genetic diseases comprises 103 CDG types, with a broad phenotypic diversity ranging from mild to severe poly‐organ ‐system dysfunction. This literature review summarizes cardiac involvement, reported in 20% of CDG. CDG with cardiac involvement were divided according to the associated type of glycosylation: N‐glycosylation, O‐glycosylation, dolichol synthesis, glycosylphosphatidylinositol (GPI)‐anchor biosynthesis, COG complex, V‐ATPase complex, and other glycosylation pathways. The aim of this review was to document and interpret the incidence of heart disease in CDG patients. Heart disorders were grouped into cardiomyopathies, structural defects, and arrhythmogenic disorders. This work may contribute to improved early management of cardiac complications in CDG.